Bioinformatic mining for RiPP biosynthetic gene clusters in Bacteroidales reveals possible new subfamily architectures and novel natural products - Fernandez-Cantos, Maria Victoria; Garcia-Morena, Diego; Yi, Yunhai; Liang, Lifeng; Gómez-Vázquez, Emilio; Kuipers, Oscar P. (Frontiers in Microbiology, 2023)
The Bacteroidales order, widely distributed among diverse human populations, constitutes a key component of the human microbiota. Members of this Gram-negative order have been shown to modulate the host immune system, play a fundamental role in the gut’s microbial food webs, or be involved in pathogenesis. Bacteria inhabiting such a complex environment as the human microbiome are expected to display social behaviors and, hence, possess factors that mediate cooperative and competitive interactions. Different types of molecules can mediate interference competition, including non-ribosomal peptides (NRPs), polyketides, and bacteriocins. The present study investigates the potential of Bacteroidales bacteria to biosynthesize class I bacteriocins, which are ribosomally synthesized and post-translationally modified peptides (RiPPs). For this purpose, 1,136 genome-sequenced strains from this order were mined using BAGEL4. A total of 1,340 areas of interest (AOIs) were detected. The most commonly identified enzymes involved in RiPP biosynthesis were radical S-adenosylmethionine (rSAM), either alone or in combination with other biosynthetic enzymes such as YcaO. A more comprehensive analysis of a subset of 9 biosynthetic gene clusters (BGCs) revealed a consistent association in Bacteroidales BGCs between peptidase-containing ATP-binding transporters (PCATs) and precursor peptides with GG-motifs. This finding suggests a possibly shared mechanism for leader peptide cleavage and transport of mature products. Notably, human metagenomic studies showed a high prevalence and abundance of the RiPP BGCs from Phocaeicola vulgatus and Porphyromonas gulae. The mature product of P. gulae BGC is hypothesized to display γ-thioether linkages and a C-terminal backbone amidine, a potential new combination of post-translational modifications (PTM). All these findings highlight the RiPP biosynthetic potential of Bacteroidales bacteria, as a rich source of novel peptide structures of possible relevance in the human microbiome context.